2014
DOI: 10.1021/ac403349c
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylation Enhancement using Diazomethane (TrEnDi): Rapid On-Column Quaternization of Peptide Amino Groups via Reaction with Diazomethane Significantly Enhances Sensitivity in Mass Spectrometry Analyses via a Fixed, Permanent Positive Charge

Abstract: Defining cellular processes relies heavily on elucidating the temporal dynamics of proteins. To this end, mass spectrometry (MS) is an extremely valuable tool; different MS-based quantitative proteomics strategies have emerged to map protein dynamics over the course of stimuli. Herein, we disclose our novel MS-based quantitative proteomics strategy with unique analytical characteristics. By passing ethereal diazomethane over peptides on strong cation exchange resin within a microfluidic device, peptides react … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 50 publications
1
63
0
Order By: Relevance
“…Wasslen and Co 38. reported that AEFVEVTK [248–256], a tryptic fragment of BSA was not detectable in MS experiment as an unmodified compound, probably due to its low ionization efficiency or low proton affinity.…”
Section: Resultsmentioning
confidence: 99%
“…Wasslen and Co 38. reported that AEFVEVTK [248–256], a tryptic fragment of BSA was not detectable in MS experiment as an unmodified compound, probably due to its low ionization efficiency or low proton affinity.…”
Section: Resultsmentioning
confidence: 99%
“…For our system, RP C18 silica was chosen to non-covalently immobilize peptide reactants, inspired by previous work using solution-solid mixed phase derivitization for proteomics. 21,22 The silica surface offers the unique conditions of site isolation of peptides, thereby disfavoring undesirable intermolecular reactions while favoring products labeled with the small molecule. In addition, the silica surface provides a unique reaction environment by co-localizing the peptide and reagents through adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Theu nique polyvalent adsorption kinetics of peptides onto reverse-phase C 18 silica allows the peptide to be adsorbed to the silica while small-molecule reagents can be added or removed through washing. [23][24][25][26] Taking advantage of the distinct differences between polyvalent versus monovalent binding kinetics, sequential reactions can be performed on an immobilized peptide while reagents can be washed away and solvents exchanged ( Figure 3). [23][24][25][26] Binding peptide substrates to reverse-phase C 18 silica allows for facile solvent transfer, introduction of small-molecule reagents,a nd removal of excess or consumed reagents,and critically allows for multiple reactions to be performed without intermediate preparative HPLC purification.…”
mentioning
confidence: 99%
“…[23][24][25][26] Taking advantage of the distinct differences between polyvalent versus monovalent binding kinetics, sequential reactions can be performed on an immobilized peptide while reagents can be washed away and solvents exchanged ( Figure 3). [23][24][25][26] Binding peptide substrates to reverse-phase C 18 silica allows for facile solvent transfer, introduction of small-molecule reagents,a nd removal of excess or consumed reagents,and critically allows for multiple reactions to be performed without intermediate preparative HPLC purification. [23] Theu tilization of reverse-phase C 18 silica, which is ubiquitous for chromatographic separation in peptide laboratories,a lso allows for the determination of washing and elution conditions by RP-HPLC.…”
mentioning
confidence: 99%